Spatiotemporal evolution characteristics of functional coupling in the triple space of the sea area of Ningbo - Wei, Baoquan; Suo, Anning; Chen, Yanlong (Frontiers in Marine Science, 2025)
IntroductionHuman socioeconomic activities flourish in coastal zones, and the rational use and protection of spatial resources and environments are vital for the sustainable development of coastal cities. To promote optimal resource allocation across ecological, residential, and production spaces (hereafter referred to as the “triple space”), an investigation into their functional coupling coordination is crucial for optimizing the allocation of ecological, living, and production space resources.MethodsIn this study, we developed an evaluation index system encompassing multiple aspects such as ecological supply and purification, residential security, and production supply. We constructed coupling coordination degree models for the triple space to quantitatively measure pairwise functional coupling and overall coordination in the coastal zone of Ningbo. Spatial characteristics and evolution patterns were analyzed using global and local Moran indexes. We analyzed the overall variation in functional coupling coordination across the coastal zone of Ningbo and correlations among evaluation units.ResultsThe findings are summarized as follows: First, a cross-coupling relationship exists with coupling coordination degrees ranging from 0.21 to 0.66 across the coastal zone of Ningbo, showing significant spatial variation (high in the south and north and low in the middle), with local coordination centers in Cixi City and Xiangshan County. Coupling coordination generally increased from 2000 to 2020. Secondly, pairwise functional coupling coordination varies, with relatively low coordination between ecology and residential areas, increasing coordination between ecology and production, and rapidly rising coordination between residential and production areas, which is currently at high levels. Third, the coupling coordination degree exhibits an overall random spatial distribution pattern without distinct clustering or discrete effects.DiscussionAccording to the local Moran index, land and sea areas of Yinzhou District show high-value polarization, failing to drive surrounding development; Zhenhai and Beilun districts exhibit low-value clustering with potential for optimization; and Cixi City and Ninghai County are high-value clustering areas, indicating strong coupling coordination. This study provides a new approach for exploring the intrinsic relationship between the different triple space functions in coastal zones and valuable reference for policy formulation and planning.